From Inferiority to Alienation in Adalet Ağaoğlu’s Fikrimin İnce Gülü - Cenk Tan (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
Adalet Ağaoğlu’s Fikrimin İnce Gülü is one of the most celebrated novels of contemporary Turkish literature. Published in 1976 and dealing with a variety of themes, the novel tells the story of Bayram, a Turkish immigrant worker’s journey from the Turkish border gate to his native village. This study aims to analyse Bayram’s narrative under two major headings: inferiority and alienation. Specifically, the article argues that the ultimate cause of Bayram’s actions is the inferiority complex which, combined with his obsessive commodity fetishism, eventually ends up with his total alienation from society. To this end, the research initially scrutinises the concept of inferiority complex through the window of individual psychology and its founder, Alfred Adler. In addition, the study also examines the notion of alienation with references to several influential thinkers. Thus, the article reveals that Bayram has become the victim of his traumatic childhood, youth experiences and social background, which give rise to his chronic feelings of inferiority. These feelings of inferiority in turn are aggravated by the capitalist system of production, eventually leading to the alienation, extreme disillusionment and isolation of Bayram as an individual. This research concludes that Bayram is an unconscious victim of his alienation and finally completes the cycle to a self-conscious state of mind after being left on his own, desperate and void of meaningful purpose orhope.